Sustainability of the Bioenergy Agricultural Frontier in the Brazilian Amazon:: an overview (Sustainability in Debate, 2015)
This study presents an overview of the sustainability levels in seven municipalities in the Brazilianstate of Pará that are included in the oil palm production zone (Elaeis guineensis Jacq.), inEastern Amazon. The area, of approximately 46,000 km², presents different patterns of landuse, and is currently considered as a priority for the implementation of the Brazilian nationalpolicy of biofuels due to its favorable edafoclimatic conditions. The study is an ex ante evaluationof the sustainability levels of the municipalities in Pará using a Sustainability Barometer - SB.The authors used quantitative data from secondary sources dated from 2010 on, all adjusted tothe conceptual framework of the SB. Sixteen indicators were used to measure human well-being(social indicators) and nine indicators for the ecological well-being (environmental indicators).Results showed that all the analysed municipalities occupy intermediate and potentially unsustainablepositions in the SB scale, which reflects the socioeconomic and environmental fragilityof the studied area.